Case Report: Eosinophilic Esophagitis in a Patient With a Novel STAT1 Gain-of-Function Pathogenic Variant - Scott, Ori; Sharfe, Nigel; Dadi, Harjit; Vong, Linda; Garkaby, Jenny; Abrego Fuentes, Laura; Willett Pachul, Jessica; Nelles, Sandra; Nahum, Amit; Roifman, Chaim M. (Frontiers in Immunology, 2022)
Background: STAT1 gain-of-function (GOF) is a primary immune dysregulatory disorder marked by wide infectious predisposition (most notably chronic mucocutaneous Candidiasis), autoimmunity, vascular disease and malignant predisposition. While atopic features have been described in some STAT1 GOF patients, they are not considered a predominant feature of the disease. Additionally, while eosinophilic gastrointestinal infiltration has been reported in some cases, this has always been described in the context of pre-existing oropharyngeal and/or esophageal Candidiasis. Clinical cases: Herein, we report 3 members of a multi-generational family diagnosed with STAT1 GOF caused by a novel mutation in the N-terminal domain, c.194A>C (p.D65A). The proband presented initially with a long-standing history of treatment-refractory eosinophilic esophagitis (EoE) without preceding gastrointestinal tract fungal infections, and her mother was diagnosed with esophagitis as well. Conclusion: EoE has been previously associated with alterations to STAT6 and STAT3 signaling pathways. The current report expands the possible association between JAK/STAT-related disorders and EoE, suggesting that EoE could be a primary disease manifestation of STAT1 GOF, even in the absence of oropharyngeal and/or esophageal Candidiasis.